STUDI LITERATUR: PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) BERBASIS MEDIA FLASH CARD DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA DI SEKOLAH DASAR - Juliana Margareta Sumila; Jini Carolina Dien (STKIP Subang, 2025)
This study aims to review the influence of the cooperative learning model STAD (Student Teams Achievement Divisions) supported by flash card media on students’ learning motivation in number concepts at elementary schools, particularly in early grades. The method used is a literature review, analyzing previous studies, scholarly articles, and relevant educational documents regarding the implementation of STAD and flash cards. Descriptive analysis was conducted to identify patterns, best practices, and factors supporting the effectiveness of these strategies. The findings indicate that the STAD model promotes positive social interaction, individual learning responsibility, and collaborative teamwork, while flash cards facilitate the understanding of number concepts in a concrete and engaging manner for students. The combination of these strategies has been shown to effectively enhance learning motivation, active participation, and student enthusiasm in mathematics learning. This study emphasizes the importance of applying cooperative learning strategies supported by visual media to foster cognitive, affective, and psychomotor development in elementary school students.